2023
DOI: 10.3390/brainsci13060945
|View full text |Cite
|
Sign up to set email alerts
|

Do Individuals with Spinal Cord Injury Benefit from Semi-Immersive Virtual Reality Cognitive Training? Preliminary Results from an Exploratory Study on an Underestimated Problem

Abstract: A spinal cord injury (SCI) is damage to any part of the spinal cord, caused by traumatic or non-traumatic events. Clinically, SCI is associated with partial or complete loss of motor, sensory, and autonomic functions below the site of injury. However, cognitive alterations in specific domains can also occur. The aim of this study was to evaluate the effects of semi-immersive virtual reality (VR) cognitive training (using the BTS Nirvana, Italy) in promoting global functional recovery in patients with SCI. Fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…This study provided evidence of benefits for both motor and cognitive outcomes [22,23]. Consequently, VR emerges as a valuable tool in promoting multi-sensory stimulation, engaging the cortical sensory-motor network and subcortical brain regions, thereby potentially enhancing motor and cognitive functions [16,17,22]. Thus, there arises the necessity to adopt an integrated approach that combines conventional rehabilitation methodologies with technological innovations, such as VR and robotics.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…This study provided evidence of benefits for both motor and cognitive outcomes [22,23]. Consequently, VR emerges as a valuable tool in promoting multi-sensory stimulation, engaging the cortical sensory-motor network and subcortical brain regions, thereby potentially enhancing motor and cognitive functions [16,17,22]. Thus, there arises the necessity to adopt an integrated approach that combines conventional rehabilitation methodologies with technological innovations, such as VR and robotics.…”
Section: Introductionmentioning
confidence: 80%
“…Indeed, in a case report and recent study [21,22], our group demonstrated the efficacy of training using a non-immersive VR system in individuals with SCI. This study provided evidence of benefits for both motor and cognitive outcomes [22,23]. Consequently, VR emerges as a valuable tool in promoting multi-sensory stimulation, engaging the cortical sensory-motor network and subcortical brain regions, thereby potentially enhancing motor and cognitive functions [16,17,22].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Exercise also acts as neuroprotective therapy. Findings of the studies have been justified with the fact that exercise-based approach cannot induce neural firing however it is believed to modulate the increased rate of spontaneous neuronal firing specific to activate the CPG for Locomotion thus justifying the synergistic effects with the better functional outcome at the end [24][25][26][27]. However, extensive variability was observed in terms of intervention dosage, frequency and variety of exercises such as intensity of activity, duration of activity, repetition of activity, number and frequency of sessions [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…By simulating real-world scenarios and activities, VR allows people to improve cognitive and motor abilities in a safe and controlled environment. Furthermore, VR holds promise in spinal cord injury rehabilitation, providing opportunities for motor and sensory retraining, as well as psychological support through immersive experiences [19]. These diverse applications highlight the potential of VR to transform neuromotor rehabilitation, offering innovative and personalized interventions tailored to individuals' unique neurological needs.…”
Section: Introductionmentioning
confidence: 99%